Enhancement of Fluoroquinolone Activity by C-8 Halogen and Methoxy Moieties: Action against a Gyrase Resistance Mutant of Mycobacterium smegmatis and a Gyrase-Topoisomerase IV Double Mutant of Staphylococcus aureus - Lu, Tao (American Society for Microbiology, 2001)
The increasing prevalence of antibiotic resistance among bacterial pathogens prompted a microbiological study of fluoroquinolone structure-activity relationships with resistant mutants. Bacteriostatic and bactericidal activities for 12 fluoroquinolones were examined with a gyrase mutant of Mycobacterium smegmatis and a gyrase-topoisomerase IV double mutant of Staphylococcus aureus. For both organisms C-8 halogen and C-8 methoxy groups enhanced activity. The MIC at which 99% of the isolates tested were inhibited (MIC(99)) was reduced three- to fivefold for the M. smegmatis mutant and seven- to eightfold for the S. aureus mutant by C-8 bromine, chlorine, and methoxy groups. With both organisms a smaller reduction in the MIC(99) (two- to threefold) was associated with a C-8 fluorine moiety. In most comparisons with M. smegmatis the response to a C-8 substituent was similar (within twofold) for wild-type and mutant cells. In contrast, mutant S. aureus was affected more than the wild type by the addition of a C-8 substituent. C-8 halogen and methoxy groups also improved the ability to kill the two mutants and the respective wild-type cells when measured with various fluoroquinolone concentrations during an incubation period equivalent to four to five doubling times. Collectively these data help define a group of fluoroquinolones that can serve (i) as a base for structure refinement and (ii) as test compounds for slowing the development of fluoroquinolone resistance during infection of vertebrate hosts.